Aplicativo multimedia para el manejo de publicidad e información en tiempo real oficina de admisiones - ESPOL - Quintana Morales, Washington David (2009)
Because of big quantity of people who were given in Admission Office of ESPOL, located in Las Peñas`s Campus, and this was the single Department in charge of the admission process , this Department has a problem in registration process, the students have a real problem because they don`t know how many spaces available have in each course, they have to go the administration office where the secretary has to know first in which course the student want to write down and then register in the system, and if the spaces were full all the process have to stop until the student decide to switch to another schedule. The project develop for Admission Office allow us to know the real space for beginner students, and they don`t have to wait too long time for the answer. At the same time we contribute to maintaining a corporate image of the university, we are projecting a fresh and dynamic image of all academic benefits of our institution through spot of different university careers while the people wait for the turn to be attended. For the development of this project we investigate technical details of multimedia, which had not been applied before, this investigation will benefit our institution and it will allow create other solutions for people who wants to continue investigate about this project. Is our desire that this database and all the investigations in this project to create new solutions for different needs in our environment, like dynamic banners in shopping centers or institutions who wants to promote their products or professional services in strategic places.